Голос большого города: рассказы : [перевод с английского] / О. Генри - Генри О. (Удмуртия, 1980)
Экземпляры: ф. 2 (20161209) / Инвентарный номер: 105157 / Цена: 10.00 / Авт.знак: Г 34 / ГРНТИ: 17.82 / ББК: 84(7Сое)